2021
DOI: 10.1016/j.celrep.2020.108660
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ boosting reduces age-associated amyloidosis and restores mitochondrial homeostasis in muscle

Abstract: Aging is characterized by loss of proteostasis and mitochondrial homeostasis. Here, we provide bioinformatic evidence of dysregulation of mitochondrial and proteostasis pathways in muscle aging and diseases. Moreover, we show accumulation of amyloid-like deposits and mitochondrial dysfunction during natural aging in the body wall muscle of C. elegans, in human primary myotubes, and in mouse skeletal muscle, partially phenocopying inclusion body myositis (IBM). Importantly, NAD + homeostasis is critical to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 59 publications
5
49
0
1
Order By: Relevance
“…Abundant literature has described an age-dependent impairment of mitochondrial function, and an alteration of mitochondrial structure across species from yeast to humans, which in turn contributes to age-associated cellular quality control decline and tissue dysfunction [ 38 , 39 ]. Though dysregulation of mitochondrial homeostasis is a global hallmark of aging, there are tissues in which it is more prominently observed.…”
Section: Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Abundant literature has described an age-dependent impairment of mitochondrial function, and an alteration of mitochondrial structure across species from yeast to humans, which in turn contributes to age-associated cellular quality control decline and tissue dysfunction [ 38 , 39 ]. Though dysregulation of mitochondrial homeostasis is a global hallmark of aging, there are tissues in which it is more prominently observed.…”
Section: Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…Though dysregulation of mitochondrial homeostasis is a global hallmark of aging, there are tissues in which it is more prominently observed. These typically include post-mitotic and highly metabolic tissues, such as skeletal muscle, which are therefore more sensitive to the dysregulation of mitochondrial-mediated processes [ 38 , 40 ]. Hence, it is not surprising that altered mitochondrial homeostasis has been long suggested as key player in the development of sarcopenia.…”
Section: Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…HRI adds a phosphate group to the protein eIF2α, and this phosphorylation slows the synthesis of most cellular proteins from messenger RNA, mediated by the ribosome complex, but promotes the production of the transcription factors ATF4, ATF5 and CHOP. Treatments that activate the UPR mt have been shown to ameliorate mitochondrial function in amyloid-β proteotoxic diseases, such as Alzheimer’s disease [ 44 ], age-associated amyloidosis [ 45 ], and kidney injury [ 46 ]. Conversely, tuning the chronic integrated stress response activation might potentially rescue synaptic plasticity loss [ 47 ], and reverse age-related cognitive decline [ 48 ], and sepsis-induced kidney injury [ 49 ].…”
Section: Mitochondria: From Structure To Physiology To Organelle Quality Controlmentioning
confidence: 99%
“…Sarcopenia is often associated with physical frailty, 23 reduced muscle function, 27 and mitochondrial dysfunction. 14 In addition, recent studies revealed that amyloidosis in skeletal muscle is associated with mitochondrial dysfunction 28 , 29 and muscle diseases including inclusion body myositis, 30 , 31 indicating that both mitochondrial dysfunction and amyloidosis may trigger sarcopenia. In group γ, which generated a negative cluster against both groups α and β, most of the HPO terms were related to neoplasms.…”
Section: Discussionmentioning
confidence: 99%